A low percentage of metastases in deep brain and temporal lobe structures. Issue 5 (23rd January 2019) - Yanagihara, Ted K; McFaline-Figueroa, J Ricardo; Giacalone, Nicholas J; Lee, Albert W; Soni, Vikram; Hwang, Mark E; Hsieh, Kristin T; Saraf, Anurag; Wu, Cheng-Chia; Yang, Daniel; Wen, Patrick Y; Ashamalla, Hani; et al.
Abstract: Background: Whole-brain radiotherapy (WBRT) in patients with brain metastases (BM) is associated with neurocognitive decline. Given its crucial role in learning and memory, efforts to mitigate this toxicity have mostly focused on sparing radiation to the hippocampus. We hypothesized that BM are not evenly distributed across the brain and that several additional areas may be avoided in WBRT based on a low risk of developing BM. Methods: We contoured 2757 lesions in a large, single-institution database of patients with newly diagnosed BM. BM centroids were mapped onto a standard brain atlas of 55 anatomic subunits and the observed percentage of BM was compared with what would be expected based on that region's volume. A region of interest (ROI) analysis was performed in a validation cohort of patients from 2 independent institutions using equivalence and one-sample hypothesis tests. Results: The brainstem and bilateral thalami, hippocampi, parahippocampal gyri, amygdala, and temporal poles had a cumulative risk of harboring a BM centroid of 4.83% in the initial cohort. This ROI was tested in 157 patients from the validation cohort and was found to have a 4.1% risk of developing BM, which was statistically equivalent between the 2 groups ( P < 1 × 10 –6, upper bound). Conclusion: Several critical brain structures are at a low risk of developing BM. A risk-adapted approach to WBRT is worthy of further investigation and may mitigate the toxicities of conventional radiation.